GENERIC STRUCTURE DEVELOPMENT ON UPPER SECONDARY SCHOOL STUDENTS’ PERSONAL ANECDOTE RECOUNT WRITING TEXTS THROUGH SFL (SYSTEMIC FUNCTIONAL LINGUISTICS) GENRE-BASED APPROACH - Mingsakoon, Pajonsak; Srinon, Udomkit (Life Sciences and Environment Journal, 2019)
This paper reports on the case study of teaching writing recounts for the English as a Foreign Language (EFL) Thai upper secondary school students using Systemic Functional Linguistics (SFL) genre-based approach at Hunkhapittayakom secondary school, Hunkha district, Chainat province, Thailand, in the second semester of the academic year 2015. The purpose of the study was to analyze students’ generic structure development on personal recount texts through the SFL perspective. Teaching of personal anecdote recount genre using the teaching-learning cycle of the SFL genre-based approach was employed of 26, 2nd year upper secondary school students of a special science-math program. The analysis of the students’ pretest writing texts discovered that their writing products were non-conformed to the stages of recount writing, and the themes were sidetracked from the topic. Subsequently, students were instructed by using the SFL genre-based approach. Comparing to the modeling texts of the literature review and the pretest texts at the commencement of the course, the analysis demonstrated that their personal anecdote recounts were positively developed with a higher degree of generic structure construction in terms of conformity and thematic reconstruction. The study suggests that the teaching cycling applied from SFL genre-based approach promoted students’ creating and understanding about text organization and writing skills.